Effects of Noradrenaline and Dopamine on supraspinal fatigue in well-trained men - Klass, M.; Roelands, B.; Lévénez, M.; Fontenelle, V.; Pattyn, N.; Meeusen, R.; Duchateau, J. (Medicine & Science in Sports & Exercise, 2012)
Purpose: Prolonged exhaustive exercise induces a failure of the nervous system to activate the involved muscles maximally (i.e., central fatigue). Part of central fatigue may reflect insufficient output from the motor cortex (i.e., supraspinal fatigue), but the cause is unresolved. To investigate the potential link between supraspinal fatigue and changes in brain concentration of dopamine and noradrenaline in temperate environment, we combined neurophysiological methods and pharmacological manipulation of these two neurotransmitters.